Highly Structured Polyvinyl Alcohol Porous Carriers: Tuning Inherent Stability and Release Kinetics in Water - Sonego, Juan Manuel (2018)
Polyvinyl alcohol (PVA) porous carriers were prepared by means of ice templating of aqueous solutions containing of 90 kD and/or 16 kD PVA. The carriers were loaded with traces of a colored probe (methyl orange) to screen their release properties, once immersed in water. The carriers prepared from solutions containing 90 kD and 16 kD PVA resulted in intimate polymer mixtures, exhibiting physical properties that stand in between those of the bare 90 kD or 16 kD PVA end members. The freezing protocols employed were adapted to prepare carriers textured in the form of either monolithic scaffolds (directional constant freezing rate) or millimetric pellets (flash-freeze). Monolithic carriers remain stable in aqueous solution, and the probe release is governed by a swelling-diffusion mechanism. The kinetics of probe release can be tuned from minutes to hours by either increasing the total PVA content or the 90 kD-to-16 kD PVA ratio in the parent solution. In contrast, pellets (millimetric carriers) immersed in water release the probe on the scale of minutes, irrespective of the PVA content or composition. However, the PVA content and the 90 kD-to-16 kD PVA ratio dramatically affect the stability of the carriers. Depending on the formulation, these small carriers can develop swelling, erosion, or eventually massive dissolution.